Ulcerative colitis: no rise in mortality in a European-wide population based cohort 10 years after diagnosis. Issue 4 (6th October 2006) - Höie, O; Schouten, L J; Wolters, F L; Solberg, I C; Riis, L; Mouzas, I A; Politi, P; Odes, S; Langholz, E; Vatn, M; Stockbrügger, R W; Moum, B
Abstract : Background: Population based studies have revealed varying mortality for patients with ulcerative colitis but most have described patients from limited geographical areas who were diagnosed before 1990. Aims: To assess overall mortality in a European cohort of patients with ulcerative colitis, 10 years after diagnosis, and to investigate national ulcerative colitis related mortality across Europe. Methods: Mortality 10 years after diagnosis was recorded in a prospective European-wide population based cohort of patients with ulcerative colitis diagnosed in 1991–1993 from nine centres in seven European countries. Expected mortality was calculated from the sex, age and country specific mortality in the WHO Mortality Database for 1995–1998. Standardised mortality ratios (SMR) and 95% confidence intervals (CI) were calculated. Results: At follow-up, 661 of 775 patients were alive with a median follow-up duration of 123 months (107–144). A total of 73 deaths (median follow-up time 61 months (1–133)) occurred compared with an expected 67. The overall mortality risk was no higher: SMR 1.09 (95% CI 0.86 to 1.37). Mortality by sex was SMR 0.92 (95% CI 0.65 to 1.26) for males and SMR 1.39 (95% CI 0.97 to 1.93) for females. There was a slightly higher risk in older age groups. For disease specific mortality, a higher SMR was found only for pulmonary disease. Mortality by European region was SMR 1.19 (95% CI 0.91 to 1.53) for the north and SMR 0.82 (95% CI 0.45–1.37) for the south. Conclusions: Higher mortality was not found in patients with ulcerative colitis 10 years after disease onset. However, a significant rise in SMR for pulmonary disease, and a trend towards an age related rise in SMR, was observed.